2008
DOI: 10.1021/ol8002578
|View full text |Cite
|
Sign up to set email alerts
|

α-Arylation of Esters Catalyzed by the Pd(I) Dimer {[P(t-Bu)3]PdBr}2

Abstract: Conditions for the coupling of bromoarenes with esters using a single base and catalyst with improved turnover numbers are described. These general conditions were made possible by using the Pd(I) catalyst {[P(t-Bu)3]PdBr}2. Reactions of acetates, propionates, and isobutyrates are presented, and reactions of all three classes of esters on a 10 g scale are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 19 publications
2
31
0
3
Order By: Relevance
“…Although a variety of electronically varied aryl bromides reacted with the alkali metal enolates in good yields, 25,27,28 the coupling of alkali metal enolates of methyl isobutyrate with ortho -substituted aryl bromides do not occur. Furthermore, the high nucleophilicity of alkali metal enolates of methyl isobutyrate limits reactions of aryl bromides containing electrophilic functionality.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although a variety of electronically varied aryl bromides reacted with the alkali metal enolates in good yields, 25,27,28 the coupling of alkali metal enolates of methyl isobutyrate with ortho -substituted aryl bromides do not occur. Furthermore, the high nucleophilicity of alkali metal enolates of methyl isobutyrate limits reactions of aryl bromides containing electrophilic functionality.…”
Section: Introductionmentioning
confidence: 98%
“…15,16 A variety of reactions of ketone, 17-22 ester, 23-28 amide, 29-32 and aldehyde 33,34 enolates have now been reported, but the use of strongly basic and nucleophlic alkali metal enolates limits the scope of these reactions. In addition, the arylated product, which is more acidic than the reactant, quenches the starting enolate, and products from undesired diarylation have formed.…”
Section: Introductionmentioning
confidence: 99%
“…Pd I -Komplexe, obwohl gegenwärtig nicht sehr geläufig, sind isolierbare dimere Spezies, die in Buchwald-HartwigAminierungen [10] und Enolat-Arylierungen Anwendung gefunden haben; [11] Die umgekehrte Reaktion, die polare MarkownikowAddition von HCl an Olefine, wird trotz der Nützlichkeit von Alkylchloriden kaum in der Synthese angewendet. Carreira und Gaspar berichteten jetzt über eine cobaltkatalysierte Addition, die wahrscheinlich über Radikalintermediate verläuft (Schema 6).…”
unclassified
“…Mechanistic investigations confirmed that the generated enolate participated in the palladium-catalyzed coupling cycle, giving the α-arylated product. Later, [PdBrP(t-Bu) 3 ] 2 was also found to catalyze gram-scale α-arylation of methyl and t-butyl esters with aryl bromides under the conditions of method B [25].…”
Section: Cross-coupling Reactions Of Lithium Enolatesmentioning
confidence: 99%